2014
DOI: 10.1002/jbmr.2316
|View full text |Cite
|
Sign up to set email alerts
|

Combined MEK Inhibition and BMP2 Treatment Promotes Osteoblast Differentiation and Bone Healing in Nf1Osx−/− Mice

Abstract: Neurofibromatosis type I (NF1) is an autosomal dominant disease with an incidence of 1/3000, caused by mutations in the NF1 gene, which encodes the RAS/GTPase-activating protein neurofibromin. Non-bone union following fracture (pseudarthrosis) in children with NF1 remains a challenging orthopedic condition to treat. Recent progress in understanding the biology of neurofibromin suggested that NF1 pseudarthrosis stems primarily from defects in the bone mesenchymal lineage and hypersensitivity of hematopoietic ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
35
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(37 citation statements)
references
References 35 publications
1
35
0
1
Order By: Relevance
“…Conversely, levels of type II collagen and aggrecan remained unaffected by TRPM7 silencing during ATDC5 cell proliferation, suggesting that TRPM7 expression, although essential for chondrocyte hypertrophy, may not be critical for chondrocyte proliferation. In addition, osteoblast cells arise from osteoprogenitor cells located in the bone marrow, and their proliferation and differentiation has been implicated in bone formation and remodeling (20)(21)(22). It has been reported that intracellular Ca 2+ or Mg 2+ homeostasis, maintained through TRPM7 expression, was important for osteoblast proliferation, migration and differentiation (12).…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, levels of type II collagen and aggrecan remained unaffected by TRPM7 silencing during ATDC5 cell proliferation, suggesting that TRPM7 expression, although essential for chondrocyte hypertrophy, may not be critical for chondrocyte proliferation. In addition, osteoblast cells arise from osteoprogenitor cells located in the bone marrow, and their proliferation and differentiation has been implicated in bone formation and remodeling (20)(21)(22). It has been reported that intracellular Ca 2+ or Mg 2+ homeostasis, maintained through TRPM7 expression, was important for osteoblast proliferation, migration and differentiation (12).…”
Section: Discussionmentioning
confidence: 99%
“…Multiple signals, such as growth/hormone factor stimulation and matrix-integrin binding, activate the Erk pathway in bone. Activated Erk promotes calvarial osteoblast differentiation through the downstream transcription factor Runx2 at Ser 301 and Ser 319 residues, and the mRNA levels of specific osteoblast differentiation-related marker genes are increased123456.…”
mentioning
confidence: 99%
“…However, because Nf1 −/− mice are embryonic lethal, follow-up studies focused on creating many tissue-specific biallelic deletions of Nf1 . These models recapitulate several phenotypes observed in humans, including bowing of the tibia, impaired bone strength and short stature ( de la Croix Ndong et al, 2014 , 2015 ; El Khassawna et al, 2012 ; Kolanczyk et al, 2007 ; Kossler et al, 2011 ; Rhodes et al, 2013 ; Schindeler et al, 2008 ; Wang et al, 2011 ; Zhang et al, 2011 ). Some of these phenotypes might be caused by increased levels of pyrophosphate, a strong inhibitor of bone mineralization.…”
Section: Neurofibromatosis Typementioning
confidence: 74%